Unlocking potential: exploring the interplay between entrepreneurship and research competence across diverse academic disciplines - Medne, Dace; Lastovska, Agnese; Lama, Gatis; Grava, Jana (Frontiers in Education, 2024)
This study aims to identify and analyze the self-assessment of entrepreneurship sub-competences among students at Latvian higher education institutions. The research questions addressed include: What is the self-assessment of students' entrepreneurship competence at different levels of education? How and to what extent does the self-assessment of students' entrepreneurship competence vary across different thematic groups? How and to what extent does the self-assessment of students' entrepreneurship competence differ between academic and professional programs? Do bachelor's and Master's students' entrepreneurship competences improve during the study process? Additionally, the study explores the correlation between students' self-assessment of their entrepreneurship competence and their research competence. The results show that students evaluated their entrepreneurship competence just above average. Bachelor-level students improved their entrepreneurship competences during their studies, but there were no statistically significant differences between Master's students' evaluations in their first and last study years. Network analysis indicates that the entrepreneurship sub-competence "Identification, mobilization, and efficient use of internal and external resources" is connected with most research competence dimensions, and improving this sub-competence will therefore have the most effect on influencing research competence.